Enhancing rainwater-use efficiency and stabilizing productivity of rainfed upland through rice (Oryza sativa)-based intercropping - KAR, GOURANGA; VERMA, H N; SINGH, R (The Indian Journal of Agricultural Sciences, 2011)
When rice yield was badly affected in light-textured upland and its sole crop cultivation was found uneconomical due to occurrence ofdry spell in 'first crop season, intercropping ofrice with pigeonpea (Cajanus cajan (L.) Millsp), blackgram (Phaseolus mungo L.) and groundnut (Arachis hypogaea L.) gave total yield of 1 781, 1 600 and 1 605 kg/ha with net economic return ofRs 10 476 ha, Rs 5 560/ha and Rs 5 880/ha respectively under integrated weed-management practices. Rainwater or rainwater use efficiency (in terms of riceequivalent weight) ofthat year enhanced from 2.2 kg/ha/mm in sole rice to 4.35 kg ha/mm in rice + pigeonpea and 4.35 kg ha/mm in rice +blackgram intercropping under that treatment. During the second year (rainy season 2001) with well assured, unifonnly distributed rainfall and integrated weed management practices, sole rice gave only Rs 5 500/ ha net economic return while its intercropping with legumes enhanced net economic return from Rs 11 040/hato 14 440lha in different intercropping combinations. During the second year, under integrated weed management treatment, rainwater-use efficiency were 2.53,3.43, 4.40 and 3.93 kg ha/mm in sole rice, rice+pigeonpea, rice + blackgram and rice+groundnut, respectively.